A high-strength and high-toughness steel material for anchor rod and its processing technology

通过对锚杆材料进行奥氏体合金钢的高温锻造、固溶时效处理,并结合自修复水性聚氨酯乳液和复合埃洛石纳米管制备防护涂料,解决了锚杆材料在复杂环境中腐蚀和涂 The problem of poor wear resistance of the layer achieves high strength and high toughness, wear resistance, superhydrophobicity, and long-term corrosion resistance.

CN118879108BActive Publication Date: 2025-02-11GUANGDONG ZHENKE DISASTER PREVENTION TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410982698.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2025-02-11
Estimated Expiration
2044-07-22

AI Technical Summary

Technical Problem

Existing anchor materials are prone to corrosion in complex environments, poor wear resistance of the coating and cannot provide continuous protection.

Method used

A vacuum induction furnace is used to melt the austenitic alloy steel, and after solid solution, aging treatment and matte polishing, protective coating is prepared in combination with self-healing aqueous polyurethane emulsion and composite Elostone nanotubes, and coated on the surface of the steel.

Benefits of technology

High-strength, high-strength, wear-resistant, super-hydrophobic, long-term corrosion-resistant steel surfaces are prepared, which extends the service life and increases the self-healing rate of protective coatings.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of steel materials, in particular to a high-strength and high-toughness steel material for anchor rods and a processing technology thereof. Austenitic alloy steel is selected as a substrate, and its solid solution aging treatment process parameters are controlled; a self-repairing waterborne polyurethane emulsion is prepared as a base material for a protective coating, polycarbonate diol and isophorone diisocyanate are used as raw materials, a prepolymer is obtained under the catalysis of dibutyltin dilaurate, dimethylolpropionic acid is used as a hydrophilic chain extender, green raw material castor oil is used as an internal cross-linking agent, 2,2'-dithiodiethanol is used as a chain extender, an amino compound containing borate is used as a modifier, and ethylenediamine is used as a neutralizer to prepare the steel material; and composite halloysite nanotubes are used as a filler for the protective coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of steel materials, in particular to a high-strength and high-toughness steel material for anchor rods and a processing technology thereof. Background Art

[0002] Anchoring technology is widely used in foundation pit support, slope reinforcement and other projects. With the progress of society, the requirements for anchoring technology are becoming more and more stringent. Anchor rods are important components of anchoring technology, and their safety and reliability are very important to anchoring technology.

[0003] Anchor construction areas are mostly outdoors in complex environments, facing a relatively severe service environment. They will inevitably face a series of corrosion problems such as rain, biological and microbial corrosion. The simplest and most cost-effective way to solve metal corrosion is to apply a coating to build protection. With the continuous enhancement of environmental awareness, more stringent requirements are also put forward for the use of coatings. Water-based polyurethanes that do not produce volatile organic compounds during use have received more and more attention. However, the coatings formed by existing coatings also have poor wear resistance and cannot continue to provide protection after damage. The preparation of a high-strength, high-toughness, long-term corrosion-resistant steel for anchors has practical significance and economic value. Summary of the invention

[0004] The object of the present invention is to provide a high-strength and high-toughness steel material for anchor rods and a processing technology thereof, so as to solve the problems in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A processing technology for high-strength and high-toughness steel for anchor rods comprises the following steps:

[0007] S1: A vacuum induction furnace is used to melt austenitic alloy steel, forged and formed to obtain a base material;

[0008] S2: performing solution treatment, aging treatment, grinding, polishing, alkali washing, acid washing, water washing, and drying on the substrate in sequence to obtain a pretreated substrate;

[0009] S3: Preparation of protective coatings using self-healing waterborne polyurethane emulsion and composite halloysite nanotubes;

[0010] S4: coating the protective coating onto the pretreated substrate and curing the coating to obtain a high-strength and high-toughness steel material for anchor rods.

[0011] Furthermore, the working conditions for forging are: temperature of 1150-1160°C and forging ratio of 8.9-9.1.

[0012] Furthermore, the working conditions of the solution treatment are: keeping at 1190-1210°C for 110-130min, water quenching to 18-25°C; the working conditions of the aging treatment are: keeping at 620-650°C for 1-2h, keeping at 680-700°C for 1-2h, keeping at 720-750°C for 1-2h, and air cooling to 18-25°C.

[0013] Furthermore, the mass ratio of the composite halloysite nanotubes to the self-repairing waterborne polyurethane emulsion is 9.5-13.6%.

[0014] Further, the preparation of composite halloysite nanotubes comprises the following steps:

[0015] (1) 8-hydroxyquinoline and ethanol are mixed, halloysite nanotubes are added, ultrasonic treatment is performed for 10-20 minutes, the mixture is transferred to a vacuum drying oven and vacuumed for 1-2 hours before being taken out, the vacuuming and taking out process is repeated 3-5 times, centrifugation, washing, drying, and grinding are performed to obtain pretreated halloysite nanotubes;

[0016] (2) Under a nitrogen atmosphere, epoxy-terminated polydimethylsiloxane and isopropanol are mixed, a mixed solution of an amino compound containing a borate ester and isopropanol is added, the temperature is raised to 48-52° C. and kept warm for 2-3 hours, a mixed solution of pretreated halloysite nanotubes, tetraethyl silicate, octyltriethoxysilane and isopropanol is added, the mixture is stirred for 20-30 minutes, deionized water is added, and the mixture is kept warm for 2-3 hours to obtain composite halloysite nanotubes.

[0017] Furthermore, the preparation of the self-repairing waterborne polyurethane emulsion comprises the following steps:

[0018] Mix polycarbonate diol, isophorone diisocyanate and dibutyl tin dilaurate, heat to 68-72°C and keep in oil bath for 2-3h, add dimethylolpropionic acid, heat to 88-90°C and keep in oil bath for 1-2h, cool to 65-70°C, add castor oil, keep in oil bath for 1-2h, cool to 55-60°C, add a mixture of 2,2'-dithiodiethanol, N,N-dimethylformamide and acetone, keep in oil bath for 1-2h, add triethylamine, keep in oil bath for 20-30min, add ice water and emulsify for 1-2h, add borate-containing amino compounds and ethylenediamine, keep in oil bath for 1-2h, discharge the material to obtain a self-healing waterborne polyurethane emulsion.

[0019] Furthermore, the mass ratio of the epoxy-terminated polydimethylsiloxane, the borate-containing amino compound, the pretreated halloysite nanotubes, tetraethyl silicate, and octyltriethoxysilane is 5:3:1.2:2.2:3.4.

[0020] Furthermore, the mass ratio of polycarbonate diol, isophorone diisocyanate, dimethylol propionic acid, castor oil, 2,2'-dithiodiethanol, and borate-containing amino compound is 25:26:5:2:4:3.

[0021] Furthermore, the preparation of the borate-containing amino compound includes the following steps: mixing anhydrous magnesium sulfate, 3-aminophenylboric acid and methanol, adding a mixed solution of methanol and 3-amino-1,2-propanediol, keeping warm at 18-25° C. for 22-24 hours, rotary evaporating, and drying to obtain the borate-containing amino compound.

[0022] Beneficial effects of the present invention:

[0023] The present invention provides a high-strength and high-toughness steel material for anchor rods and a processing technology thereof. Through composition and process design, a high-strength, high-toughness, long-term corrosion-resistant steel material for anchor rods with a wear-resistant and super-hydrophobic surface is prepared.

[0024] In the present invention, an austenitic alloy steel containing elements such as Nb, Si, Al, V, and Mn is selected as a substrate, and by controlling the process parameters of its solid solution aging treatment, a precipitate phase that maintains a certain coherent or semi-coherent orientation relationship with austenite is dispersed in the matrix, thereby effectively pinning movable dislocations and improving the strength of the austenitic alloy steel.

[0025] In order to give the steel surface excellent wear resistance and mechanical damage resistance, and give the steel surface long-term corrosion resistance, a self-healing waterborne polyurethane emulsion was prepared as the base material of the protective coating. Polycarbonate diol and isophorone diisocyanate were used as raw materials, and a prepolymer was obtained under the catalysis of dibutyltin dilaurate. Dimethylolpropionic acid was used as a hydrophilic chain extender, green raw material castor oil was used as an internal cross-linking agent, 2,2'-dithiodiethanol was used as a chain extender, an amino compound containing borate ester was used as a modifier, and ethylenediamine was used as a neutralizer to prepare a self-healing waterborne polyurethane emulsion, wherein the amino compound containing borate ester was prepared from 3-aminophenylboric acid and 3-amino-1,2-propylene glycol as raw materials, and the dynamic reversible borate ester in its structure and the disulfide bond in 2,2'-dithiodiethanol synergistically gave the steel self-healing ability, and it was coated on the surface of the pretreated substrate to give the steel surface hydrophobicity, wear resistance and corrosion resistance, thereby extending the service life of the steel surface.

[0026] Composite halloysite nanotubes are used as fillers for protective coatings. Cheap, easily available, and environmentally friendly halloysite nanotubes are selected as nanocontainers for the corrosion inhibitor 8-hydroxyquinoline. Halloysite nanotubes can fill the cavities formed by the coating to form crack bridges, thereby improving the anti-corrosion performance of the coating. In order to improve the uniformity of the dispersion of halloysite nanotubes in the protective coating, the pretreated halloysite nanotubes are modified, and the intermediate preparation is synthesized by the ring opening of the end epoxy polydimethylsiloxane and the amino compound containing borate. Then, the intermediate preparation is hydrolyzed and polycondensed with tetraethyl silicate and octyltriethoxysilane to load nano-hybrid siloxane with dynamic reversible bonds on the pretreated halloysite nanotubes to construct a hydrophobic and corrosion-resistant filler, which is introduced into the protective coating to give the steel surface long-term wear resistance, corrosion resistance, and hydrophobicity, thereby improving the self-repair rate of the protective coating. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.

[0029] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0030] Embodiment 1: A processing technology for high-strength and high-toughness steel for anchor rods, comprising the following steps:

[0031] S1: A vacuum induction furnace is used to melt austenitic alloy steel, forged and formed to obtain a base material;

[0032] The working conditions for forging are: temperature 1150°C, forging ratio 8.9;

[0033] S2: performing solution treatment, aging treatment, grinding, polishing, alkali washing, acid washing, water washing, and drying on the substrate in sequence to obtain a pretreated substrate;

[0034] The working conditions of solution treatment are: keep at 1190℃ for 130min, water quench to 18℃; the working conditions of aging treatment are: keep at 620℃ for 2h, keep at 680℃ for 2h, keep at 720℃ for 2h, air cool to 18℃;

[0035] S3: Preparation of protective coatings using self-healing waterborne polyurethane emulsion and composite halloysite nanotubes;

[0036] The mass ratio of composite halloysite nanotubes and self-repairing waterborne polyurethane emulsion is 9.5%;

[0037] The preparation of the composite halloysite nanotubes comprises the following steps:

[0038] (1) 2 g of 8-hydroxyquinoline and 50 mL of ethanol were mixed, 1 g of halloysite nanotubes were added, and the mixture was ultrasonically treated for 10 min. The mixture was transferred to a vacuum drying oven and vacuumed for 1 h before being taken out. The vacuuming and taking out process was repeated 3 times. The mixture was centrifuged, washed, dried, and ground to obtain pretreated halloysite nanotubes.

[0039] (2) Under a nitrogen atmosphere, 5 g of epoxy-terminated polydimethylsiloxane and 20 mL of isopropanol were mixed, 3 g of a borate-containing amino compound and 15 mL of isopropanol were added, the temperature was raised to 48 ° C and kept warm for 3 h, 1.2 g of pretreated halloysite nanotubes, 2.2 g of tetraethyl silicate, 3.4 g of octyltriethoxysilane and 10 mL of isopropanol were added, the mixture was stirred for 20 min, 2 mL of deionized water was added, and the mixture was kept warm for 2 h to obtain composite halloysite nanotubes;

[0040] The preparation of the self-repairing waterborne polyurethane emulsion comprises the following steps:

[0041] Mix 25g of polycarbonate diol, 26g of isophorone diisocyanate, and 3 drops of dibutyltin dilaurate, heat to 68°C and keep in an oil bath for 3h, add 5g of dimethylolpropionic acid, heat to 88°C and keep in an oil bath for 2h, cool to 65°C, add 2g of castor oil, keep in an oil bath for 1h, cool to 55°C, add a mixture of 4g of 2,2'-dithiodiethanol, 5mL of N,N-dimethylformamide, and 3mL of acetone, keep in an oil bath for 1h, add 1g of triethylamine, keep in an oil bath for 20min, add 200g of ice water and emulsify for 1h, add 3g of borate-containing amino compounds and 0.5g of ethylenediamine, keep in an oil bath for 1h, discharge, and obtain a self-healing waterborne polyurethane emulsion;

[0042] The preparation of the borate-containing amino compound comprises the following steps:

[0043] 5 g of anhydrous magnesium sulfate, 6.9 g of 3-aminophenylboronic acid, and 25 mL of methanol were mixed, and a mixture of 12.5 mL of methanol and 4.6 g of 3-amino-1,2-propylene glycol was added, and the mixture was kept at 18° C. for 24 h, and rotary evaporated and dried to obtain an amino compound containing a borate ester;

[0044] S4: coating the protective coating onto the pretreated substrate and curing the coating to obtain a high-strength and high-toughness steel material for anchor rods.

[0045] Embodiment 2: A processing technology for high-strength and high-toughness steel for anchor rods, comprising the following steps:

[0046] S1: A vacuum induction furnace is used to melt austenitic alloy steel, forged and formed to obtain a base material;

[0047] The working conditions for forging are: temperature 1155°C, forging ratio 9;

[0048] S2: performing solution treatment, aging treatment, grinding, polishing, alkali washing, acid washing, water washing, and drying on the substrate in sequence to obtain a pretreated substrate;

[0049] The working conditions of solution treatment are: keep at 1200℃ for 120min, water quench to 20℃; the working conditions of aging treatment are: keep at 630℃ for 1.5h, keep at 690℃ for 1.5h, keep at 730℃ for 1.5h, air cool to 20℃;

[0050] S3: Preparation of protective coatings using self-healing waterborne polyurethane emulsion and composite halloysite nanotubes;

[0051] The mass ratio of composite halloysite nanotubes and self-repairing waterborne polyurethane emulsion is 12.1%;

[0052] The preparation of the composite halloysite nanotubes comprises the following steps:

[0053] (1) 2 g of 8-hydroxyquinoline and 50 mL of ethanol were mixed, 1 g of halloysite nanotubes were added, and the mixture was ultrasonically treated for 15 min. The mixture was transferred to a vacuum drying oven and vacuumed for 1.5 h before being taken out. The vacuuming and taking out process was repeated 4 times. The mixture was centrifuged, washed, dried, and ground to obtain pretreated halloysite nanotubes.

[0054] (2) Under a nitrogen atmosphere, 5 g of epoxy-terminated polydimethylsiloxane and 20 mL of isopropanol were mixed, 3 g of a borate-containing amino compound and 15 mL of isopropanol were added, the temperature was raised to 50° C. and kept warm for 2.5 h, 1.2 g of pretreated halloysite nanotubes, 2.2 g of tetraethyl silicate, 3.4 g of octyltriethoxysilane and 10 mL of isopropanol were added, the mixture was stirred for 25 min, 2 mL of deionized water was added, and the mixture was kept warm for 2.5 h to obtain composite halloysite nanotubes;

[0055] The preparation of the self-repairing waterborne polyurethane emulsion comprises the following steps:

[0056] Mix 25g of polycarbonate diol, 26g of isophorone diisocyanate, and 3 drops of dibutyltin dilaurate, heat to 70°C and keep in an oil bath for 2.5h, add 5g of dimethylolpropionic acid, heat to 89°C and keep in an oil bath for 1.5h, cool to 68°C, add 2g of castor oil, continue to keep in an oil bath for 1.5h, cool to 58°C, add a mixture of 4g of 2,2'-dithiodiethanol, 5mL of N,N-dimethylformamide, and 3mL of acetone, continue to keep in an oil bath for 1.5h, add 1g of triethylamine, keep in an oil bath for 25min, add 200g of ice water and emulsify for 1.5h, add 3g of borate-containing amino compounds and 0.5g of ethylenediamine, continue to keep in an oil bath for 1.5h, and discharge to obtain a self-healing waterborne polyurethane emulsion;

[0057] The preparation of the borate-containing amino compound comprises the following steps:

[0058] 5 g of anhydrous magnesium sulfate, 6.9 g of 3-aminophenylboronic acid, and 25 mL of methanol were mixed, and a mixture of 12.5 mL of methanol and 4.6 g of 3-amino-1,2-propylene glycol was added, and the mixture was kept at 20° C. for 23 h, and then rotary evaporated and dried to obtain an amino compound containing a borate ester;

[0059] S4: coating the protective coating onto the pretreated substrate and curing the coating to obtain a high-strength and high-toughness steel material for anchor rods.

[0060] Embodiment 3: A processing technology for high-strength and high-toughness steel for anchor rods, comprising the following steps:

[0061] S1: A vacuum induction furnace is used to melt austenitic alloy steel, forged and formed to obtain a base material;

[0062] The working conditions for forging are: temperature 1160°C, forging ratio 9.1;

[0063] S2: performing solution treatment, aging treatment, grinding, polishing, alkali washing, acid washing, water washing, and drying on the substrate in sequence to obtain a pretreated substrate;

[0064] The working conditions of solution treatment are: keep at 1210℃ for 110min, water quench to 25℃; the working conditions of aging treatment are: keep at 650℃ for 1h, keep at 700℃ for 1h, keep at 750℃ for 1h, air cool to 25℃;

[0065] S3: Preparation of protective coatings using self-healing waterborne polyurethane emulsion and composite halloysite nanotubes;

[0066] The mass ratio of composite halloysite nanotubes and self-repairing waterborne polyurethane emulsion is 13.6%;

[0067] The preparation of the composite halloysite nanotubes comprises the following steps:

[0068] (1) 2 g of 8-hydroxyquinoline and 50 mL of ethanol were mixed, 1 g of halloysite nanotubes were added, and the mixture was ultrasonically treated for 20 min. The mixture was transferred to a vacuum drying oven and vacuumed for 2 h before being taken out. The vacuuming and taking out process was repeated 5 times. The mixture was centrifuged, washed, dried, and ground to obtain pretreated halloysite nanotubes.

[0069] (2) Under a nitrogen atmosphere, 5 g of epoxy-terminated polydimethylsiloxane and 20 mL of isopropanol were mixed, 3 g of a borate-containing amino compound and 15 mL of isopropanol were added, the temperature was raised to 52 ° C and kept warm for 2 h, 1.2 g of pretreated halloysite nanotubes, 2.2 g of tetraethyl silicate, 3.4 g of octyltriethoxysilane and 10 mL of isopropanol were added, the mixture was stirred for 30 min, 2 mL of deionized water was added, and the mixture was kept warm for 3 h to obtain composite halloysite nanotubes;

[0070] The preparation of the self-repairing waterborne polyurethane emulsion comprises the following steps:

[0071] Mix 25g of polycarbonate diol, 26g of isophorone diisocyanate, and 3 drops of dibutyltin dilaurate, heat to 72°C and keep in an oil bath for 2h, add 5g of dimethylolpropionic acid, heat to 90°C and keep in an oil bath for 1h, cool to 70°C, add 2g of castor oil, keep in an oil bath for 2h, cool to 60°C, add a mixture of 4g of 2,2'-dithiodiethanol, 5mL of N,N-dimethylformamide, and 3mL of acetone, keep in an oil bath for 2h, add 1g of triethylamine, keep in an oil bath for 30min, add 200g of ice water and emulsify for 2h, add 3g of borate-containing amino compounds and 0.5g of ethylenediamine, keep in an oil bath for 2h, and discharge to obtain a self-healing waterborne polyurethane emulsion;

[0072] The preparation of the borate-containing amino compound comprises the following steps:

[0073] 5 g of anhydrous magnesium sulfate, 6.9 g of 3-aminophenylboronic acid, and 25 mL of methanol were mixed, and a mixture of 12.5 mL of methanol and 4.6 g of 3-amino-1,2-propylene glycol was added, and the mixture was kept at 25° C. for 22 h, and rotary evaporated and dried to obtain an amino compound containing a borate ester;

[0074] S4: coating the protective coating onto the pretreated substrate and curing the coating to obtain a high-strength and high-toughness steel material for anchor rods.

[0075] Comparative Example 1: Taking Example 3 as the control group, the self-repairing water-based polyurethane emulsion was replaced with water-based polyurethane (BZ-7: Changzhou Baichang Coatings Technology Co., Ltd.), and the other processes were normal.

[0076] Comparative Example 2: Taking Example 3 as the control group, the composite halloysite nanotubes were replaced with halloysite nanotubes, and the other processes were normal.

[0077] Comparative Example 3: Example 3 was used as a control group, in which no borate-containing amino compound was prepared, and other processes were normal.

[0078] The protective coatings in the examples and comparative examples were formed to a thickness of 200 μm.

[0079] Sources of raw materials used (for demonstration purposes only):

[0080] In terms of mass percentage, the composition of austenitic alloy steel is: Cu1.62%, Mo4.3%, Cr9.2%, Ni4.4%, Nb0.5%, C0.22%, Si0.43%, Al0.5%, V1.5%, W1.8%, Mn3.75%, and the balance is Fe; terminal epoxy polydimethylsiloxane 102782-97-8: (Alpha) Zhengzhou Alpha Chemical Co., Ltd.; polycarbonate diol YK1330: Hubei Yongkuo Technology Co., Ltd.; 2,2'-dithiodiethanol 1892-29-1: Guangdong Zhonghe High-tech Co., Ltd.; 8-hydroxyquinoline H104638, halloysite Nanotubes H431905, tetraethyl silicate T110593, octyltriethoxysilane T107262, isophorone diisocyanate I109582, dibutyltin dilaurate D100274, dihydroxymethylpropionic acid B104539, castor oil C110663, N,N-dimethylformamide D111999, triethylamine T103285, ethylenediamine E112132, M116443, anhydrous magnesium sulfate, 3-aminophenylboronic acid A111311, 3-amino-1,2-propylene glycol A107504: Aladdin reagent; methanol, ethanol, isopropanol, acetone, analytical grade: Sinopharm reagent.

[0081] Performance test: The steel materials prepared in the embodiments and comparative examples were subjected to performance tests:

[0082] Tensile strength and elongation at break: The tensile test was conducted using a WDW-100 microcomputer-controlled electronic universal testing machine. The sample size was a round bar with a diameter of 5 mm and a length of 25 mm, and the clamping end was processed into an M10 thread.

[0083] Hydrophobicity: The water contact angle was measured using a contact angle meter and tested with a 4 μL deionized water droplet;

[0084] Self-repairing property: construct a scratch with a length of 1 cm, a width of 4 μm, and a depth of 200 μm on the surface, keep it at 90°C for 12 hours, and observe the scratch length under an electron microscope. The self-repairing rate = (L 初始划痕长度 -L 现有划痕长度 ) / L 初始划痕长度×100%;

[0085] Adhesion test: refer to the 100-grid method, draw a uniform 100-grid pattern on the surface, flatten the grid area with a tape that exceeds the grid by 18mm, and tear off the tape at a uniform speed within 5 minutes; the rating standard is: the incision edge is smooth and there is no peeling: 0 level, there is peeling at the incision and the grid damage area is less than 5%: 1 level, the grid damage area is 5-15%: 2 level, the grid damage area is 15-35%: 3 level, the grid damage area is 35-65%: 4 level, the grid damage area is greater than 65%: 5 level;

[0086] Abrasion resistance: Under a pressure of 1kg, rub with 1200-grit sandpaper for 50 friction cycles, and each friction of 1cm in the horizontal and vertical directions is considered as one cycle. Then test the water contact angle again and calculate the change rate of the water contact angle. When the change rate of the water contact angle is less than 2% (including 2%), it is excellent, otherwise it is unqualified;

[0087] Salt spray resistance: refer to GB / T1771-2007, the temperature in the salt spray chamber is 36℃, the pH is 6.9, the sodium chloride concentration is 59g / L, and there is no blistering, damage, corrosion and other phenomena after 120 days, which is excellent, otherwise it is unqualified; the results are shown in Table 1;

[0088] Table 1

[0089] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Tensile strength(MPa) 1191 1198 1203 / / / Elongation at break (%) 26.7 26.9 27.2 / / / Water contact angle (°) 151.4 151.7 152.1 148.2 143.8 146.5 Self-repair rate (%) 99.98 99.99 100 65.46 95.32 88.32 Adhesion Level 0 Level 0 Level 0 Level 1 Level 1 Level 1 Wear resistance excellent excellent excellent Failure Failure Failure Salt spray resistance (120d) excellent excellent excellent Failure Failure Failure

[0090] The present invention provides a high-strength and high-toughness steel material for anchor rods and a processing technology thereof. Through composition and process design, a high-strength, high-toughness, long-term corrosion-resistant steel material for anchor rods with a wear-resistant and super-hydrophobic surface is prepared. In Table 1, / indicates untested.

[0091] Example 3 is compared with Comparative Example 1 and Comparative Example 3. In order to give the steel surface excellent wear resistance and mechanical damage resistance, and give the steel surface long-term corrosion resistance, a self-repairing waterborne polyurethane emulsion is prepared as a base material for a protective coating. Polycarbonate diol and isophorone diisocyanate are used as raw materials, and a prepolymer is obtained under the catalysis of dibutyltin dilaurate. Dimethylolpropionic acid is used as a hydrophilic chain extender, green raw material castor oil is used as an internal cross-linking agent, 2,2'-dithiodiethanol is used as a chain extender, an amino compound containing borate is used as a modifier, and ethylenediamine is used as a neutralizer to prepare a self-repairing waterborne polyurethane emulsion, wherein the amino compound containing borate is prepared from 3-aminophenylboric acid and 3-amino-1,2-propylene glycol as raw materials, and the dynamic reversible borate and disulfide bonds in its structure synergistically give the steel a self-repairing surface, which is coated on the surface of a pretreated substrate to give the steel surface superhydrophobicity, wear resistance and corrosion resistance, thereby extending the service life of the steel surface.

[0092] Example 3 is compared with Comparative Examples 2 and 3. Composite halloysite nanotubes are used as fillers for protective coatings. Cheap, easily available, and environmentally friendly halloysite nanotubes are selected as nanocontainers for the corrosion inhibitor 8-hydroxyquinoline. The halloysite nanotubes can fill the cavities formed by the coating to form crack bridging, crack deflection, and crack bending, thereby improving the anti-corrosion performance of the coating. In order to improve the uniformity of the dispersion of halloysite nanotubes in the protective coating and to encapsulate 8-hydroxyquinoline, the pretreated halloysite nanotubes are modified, and the intermediate preparation is synthesized by the ring opening of terminal epoxy polydimethylsiloxane and borate-containing amino compounds, and then tetraethyl silicate and octyltriethoxysilane are hydrolyzed and polycondensed to load nano-hybrid siloxane with dynamic reversible bonds on the pretreated halloysite nanotubes to construct a hydrophobic and corrosion-resistant filler, which is introduced into the protective coating to extend the service life of the steel surface.

[0093] In summary, the present invention prepares a high-strength and high-toughness steel for anchor rods, which has good application prospects.

[0094] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A processing technology for high-strength and high-toughness steel for anchor rods, characterized in that: The following steps are involved: S1: A vacuum induction furnace is used to melt austenitic alloy steel, forged and formed to obtain a base material; S2: performing solution treatment, aging treatment, grinding, polishing, alkali washing, acid washing, water washing, and drying on the substrate in sequence to obtain a pretreated substrate; S3: Preparation of protective coatings using self-healing waterborne polyurethane emulsion and composite halloysite nanotubes; S4: coating the protective coating onto the pretreated substrate and curing the coating to obtain a high-strength and high-toughness steel material for anchor rods; The preparation of the composite halloysite nanotubes comprises the following steps: (1) 8-hydroxyquinoline and ethanol are mixed, halloysite nanotubes are added, ultrasonic treatment is performed for 10-20 minutes, the mixture is transferred to a vacuum drying oven and vacuumed for 1-2 hours before being taken out, the vacuuming and taking out process is repeated 3-5 times, centrifugation, washing, drying, and grinding are performed to obtain pretreated halloysite nanotubes; (2) under a nitrogen atmosphere, epoxy-terminated polydimethylsiloxane and isopropanol are mixed, a mixed solution of an amino compound containing a borate ester and isopropanol is added, the temperature is raised to 48-52° C. and kept warm for 2-3 hours, a mixed solution of pretreated halloysite nanotubes, tetraethyl silicate, octyltriethoxysilane and isopropanol is added, the mixture is stirred for 20-30 minutes, deionized water is added, and the temperature is kept warm for 2-3 hours to obtain composite halloysite nanotubes; In the preparation of composite halloysite nanotubes, the mass ratio of epoxy-terminated polydimethylsiloxane, borate-containing amino compound, pretreated halloysite nanotubes, tetraethyl silicate, and octyltriethoxysilane is 5:3:1.2:2.2:3.

4.

2. The processing technology of the high-strength and high-toughness steel for anchor rod according to claim 1 is characterized in that: The working conditions for forging are: temperature of 1150-1160°C and forging ratio of 8.9-9.

1.

3. The processing technology of the high-strength and high-toughness steel for anchor rod according to claim 1 is characterized in that: The working conditions of solution treatment are: keep at 1190-1210℃ for 110-130min, water quench to 18-25℃; the working conditions of aging treatment are: keep at 620-650℃ for 1-2h, keep at 680-700℃ for 1-2h, keep at 720-750℃ for 1-2h, air cool to 18-25℃.

4. The processing technology of the high-strength and high-toughness steel for anchor rod according to claim 1 is characterized in that: The mass ratio of the composite halloysite nanotubes and the self-repairing waterborne polyurethane emulsion is 9.5-13.6%.

5. The processing technology of high-strength and high-toughness steel for anchor rod according to claim 1 is characterized in that: The preparation of the self-repairing waterborne polyurethane emulsion comprises the following steps: Mix polycarbonate diol, isophorone diisocyanate and dibutyl tin dilaurate, heat to 68-72°C and keep in oil bath for 2-3h, add dimethylolpropionic acid, heat to 88-90°C and keep in oil bath for 1-2h, cool to 65-70°C, add castor oil, keep in oil bath for 1-2h, cool to 55-60°C, add a mixture of 2,2'-dithiodiethanol, N,N-dimethylformamide and acetone, keep in oil bath for 1-2h, add triethylamine and keep in oil bath for 20-30min, add ice water and emulsify for 1-2h, add borate-containing amino compounds and ethylenediamine, keep in oil bath for 1-2h, discharge the mixture to obtain a self-healing waterborne polyurethane emulsion.

6. The processing technology of the high-strength and high-toughness steel for anchor rod according to claim 5 is characterized in that: The mass ratio of polycarbonate diol, isophorone diisocyanate, dimethylol propionic acid, castor oil, 2,2'-dithiodiethanol, and borate-containing amino compound is 25:26:5:2:4:

3.

7. The processing technology of high-strength and high-toughness steel for anchor rod according to claim 1 is characterized in that: The preparation of the borate-containing amino compound comprises the following steps: mixing anhydrous magnesium sulfate, 3-aminophenylboric acid and methanol, adding a mixed solution of methanol and 3-amino-1,2-propylene glycol, keeping warm at 18-25° C. for 22-24 hours, rotary evaporating and drying to obtain the borate-containing amino compound.

8. A high-strength and high-toughness steel material for anchor rods, characterized in that: The invention is prepared by any one of the processing techniques of claims 1 to 7.

Citation Information

Patent Citations

  • Waterborne polyurethane coating

    CN109439166A

  • Self-repairing polyurethane elastomer based on multiple dynamic reversible effects, and preparation method thereof

    CN110511344A

  • Precipitation hardening type austenite alloy steel with high expansibility and thermal stability and manufacturing method thereof

    CN112301283A

  • Toughening type epoxy powder coating with self-repairing property and application thereof

    CN116285567A

  • High-hardness reinforced steel pipe and preparation process thereof

    CN117779028A